MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF TOTAL QUALITY MANAGEMENTDI SEKOLAH DASAR ISLAM TERPADU (SDIT) ULUL ALBAB 1 PURWOREJO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Â This study aims to descritse the implementation of the management of education in the Integrited Islamic Elementary School (the IIES) Ulul Albab 1 Purworejo which include; (1) planning curriculum, staffing, facilities and infrastructure, finance and public relations. (2) organizing the curriculum, staffing, facilities and infrastructure, finance and public relations. (3) the implementation of the curriculum, staffing, facilities and infrastructure, finance and public relations, and (4) evaluation of curriculum, staffing, facilities and infrastructure, finance and public relations.This study used a qualitative approach to the study site in the Integrited Islamic Elementary School (the IIES) Ulul Albab 1 Purworejo as one of the private schools that implement full day school in the district Purworejo. The method used in this study is the observation, interviews, and documentation. Analysis of the data using qualitative analysis models used Miles and Humbermen.The results showed that in general this school has implemented education with good management. It is proved that: management education covering curriculum, staffing, facilities / infrastructure, finance and public relations already planned, organized, implemented and evaluated according to the steps of Total Quality Management. Tthe activity is in order to give satisfaction to the customers. In this case students, parents, and school community are directly related.